Haikyu!! 17, Talent and instinct - Furudate, Haruichi, 1983- (Shonen Jump manga., 2017)
It's the final set of the Spring Tournament qualifier semifinals, and Aoba Johsai has game point! With their backs against the wall yet again, Karasuno digs deep and throws their greatest efforts into one final rally. Will they be able to take the rally and overcome the Great King?!